Translating Culturally Specific Items (CSIs): A Korean & English case study - Sketchley, M (2021)
This research focuses on the translation of Culturally Specific Items (CSIs) that are notoriously difficult to translate yet not widely studied in the field of Translation Studies and even less studied in Korean <> English language pair. The need for this particular research is that CSIs certainly do exist in a text that needs to be translated and those CSIs constantly hamper translators’ minds in the real world of translation, but we know so little about how they are translated in the target language. By presenting CSI translation on an empirical data basis, we shall gain a better understanding with Korean and English pair CSI translation and enhance our understanding in the provision of Korean professional translation. This research observes 8 professional Korean translators who translated text in both directions, Korean into English, and English into Korean, in an aspect of how the Korean professional translators translate Culturally Specific Items into the target language, discern the phenomena and particular tendencies detected from the 80 sets of the translated texts. This research is a rare opportunity to establish the purview of Culturally Specific Items (CSIs) in Translation Studies and to correct the scarcity of Korean CSI reference materials available in Translation Studies which is empowered by descriptive data, directly reported from the 8 professional Korean translators and the in-depth empirical data, analysed from the translated text.